Pengaruh Tayangan Drama Korea di Media Baru terhadap Minat Belajar Bahasa bagi Remaja - Putri, Assyifa Nurtasya; Abidin, Zainal; Nayiroh, Luluatu (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Since the COVID-19 pandemic hit the world, many countries have imposed restrictions on activities outside the home, so all action has been shifted to the house which has increased users of video-on-demand services. Currently, most people access it through various special applications available on their smartphones on the Google Play Store or Apple Store. This study aims to determine the effect of showing Korean dramas in new media on interest in learning the language in adolescents. The subjects of this study were teenagers from SMAN 1 SETU Kabupaten Bekasi, with a total of 115 students as respondents. This research is quantitative using explanatory survey methods and use and effect theory, which explain the relationship between mass communication communicated through mass media so that it has impact on mass media users. The results of this study indicate that Korean drama shows have an impact on interest in learning a language, with a significance value of 0.000 < 0.05 so it can be concluded that the variable showing Korean dramas (X) influences the variable interest in learning the language (Y). Keywords: Drama, Video on Demand, an Interest in Learning